Comparative In-Silico Molecular Docking of Silymarin for SARS-CoV-2 Receptor - Michael Antony Samy Amutha Gnana Arasi; Sapthasri Ravichandran; Irudayam Iayaraman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The COVID-19 pandemic has spread worldwide in over 185 countries, with millions of infections and hundreds of thousands of deaths. The current pandemic has made the situation worse, forcing the development of better treatment. In this work, the binding ability of COVID-19 receptors with silymarin has been analyzed using AutoDock 1.4.6. Further, it is compared with the standard drug remdesivir. Silymarin, a potential phytochemical compound obtained from the seeds of the Silybum marianum (milk thistle) plant, has been documented as an antiviral agent against several viruses. So silymarin can also be an effective compound in the treatment of COVID-19. This study aims to determine the binding ability of COVID-19 receptors towards silymarin and further comparative analysis by remdesivir. Drug Discovery Studio version 2021 software was used to analyze ligands and targets. AutoDock 1.4.6 software was used to perform the docking study. Among the various receptors, 5N11 (Human beta1-coronavirus (β1CoV) OC43), 7MJP (SARS-CoV-2 receptor binding domain in complex with neutralizing antibody COVA2-39), 7JMO (SARS-CoV-2 receptor-binding domain in complex with neutralizing antibody COVA2-04) receptors showed the highest binding ability of -8.09, -7.23, -6.96 kcal/mol towards silymarin compared to the standard remdesivir having the docking score of -5.21, -3.76, -2.97 kcal/mol, respectively. By the comparative analysis, silymarin has a better and highest binding ability.